ANTI-INFLAMMATORY AND DIURETIC ACTIVITY OF UNCÁRIA TOMENTOSA (CAT’S CLAW): SYSTEMATIC REVIEW. - Coelho, Larissa Jorge; Nascimento, Guilherme Nobre Lima do (REVISTA CEREUS, 2020)
To review the literature regarding studies that evaluates the anti-inflammatory and diuretic activity of Uncaria tomentosa (Willd. DC.), popularly known as cat’s claw. A search was made for scientific articles from September to August of 2017, using the descriptors: Uncaria tomentosa, cat’s claw, diuretics and anti-inflammatories, as search strategies. In vivo preclinical studies and clinical trials were included in the evaluation of the anti-inflammatory and diuretic activity of U. tomentosa. From the 165 articles found, 10 are according to the inclusion criteria, 50% (n= 05) with experimental design in the form of pre-clinical in vivo tests, clinical trials corresponded to a total of 30% (n= 03) and the sample of In vivo and in vitro pre-clinical trials were equivalent to a total of 20% (n= 02). The most studied properties of U. tomentosa are anti-inflammatory, antioxidant, immune-stimulatory, antiviral and antitumor. No studies evaluating the diuretic activity of U. tomentosa were found, and pre-clinical in vivo studies and clinical trials were necessary to evaluate this possible U. tomentosa potential.